2015
DOI: 10.4081/monaldi.2012.154
|View full text |Cite
|
Sign up to set email alerts
|

Essential amino acid supplementation in patients with severe COPD: a step towards home rehabilitation

Abstract: Background. Pulmonary Rehabilitation (“Rehabilitation”) can improve both lung function and quality of life in patients suffering from chronic obstructive pulmonary disease (COPD) even if only a very small proportion of patients have access to Rehabilitation. Supplementation of Essential Amino Acids (EAAs) might allow COPD patients to achieve some typical Rehabilitation outcomes such as a better physical performance and an improved health status. Methods. 88 COPD out-patients (GOLD class 3-4) with a body mass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 51 publications
1
56
1
Order By: Relevance
“…This could be related to specific nutrient effects on lower limb muscle metabolism resulting in decreased muscle fatigue or via the observed improvement in respiratory muscle function. Dal Negro et al 15 reported increased number of steps after EAA supplementation in domiciliary severe COPD patients. Alternatively, a positive effect of n‐3 fatty acid enriched protein‐dense supplements could be implicated as in cachectic patients with pancreatic cancer n‐3 FA supplementation also increased physical activity level assessed by doubly labelled water independent of muscle mass 24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be related to specific nutrient effects on lower limb muscle metabolism resulting in decreased muscle fatigue or via the observed improvement in respiratory muscle function. Dal Negro et al 15 reported increased number of steps after EAA supplementation in domiciliary severe COPD patients. Alternatively, a positive effect of n‐3 fatty acid enriched protein‐dense supplements could be implicated as in cachectic patients with pancreatic cancer n‐3 FA supplementation also increased physical activity level assessed by doubly labelled water independent of muscle mass 24.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, patients with advanced COPD and muscle wasting are reported to have low plasma levels of BCAAs (especially leucine) compared with age‐matched controls,7, 14 which could reflect a deficient state in muscle,7 but no evidence for a deficient BCAA state was found in our NUTRAIN patients with less advanced COPD. In a sample of 88 patients with severe COPD (GOLD 3–4) and BMI <23 kg/m 2 not receiving exercise training, 12 weeks of supplementation with an EAA (4 g/day) mixture high in leucine led to higher FFM and muscle strength compared with an isocaloric placebo 15. Nonetheless, these patients were characterized by lower protein intake at baseline (1.0 ± 0.2 g/kg) than the current study population (1.4 ± 0.1 g/kg BW).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results show positive effects of EAAs on exercise intolerance. In Tables 1 and 2, the amino acid mixture used in these studies and their respectively changes in certain exercise variables after chronic amino acid supplementation are reported, after evaluation from the original investigations [810]. …”
Section: Eaa-induced Exercise Improvements In Chf/copd and Their Mmentioning
confidence: 99%
“…Some studies [710] have found that chronic oral supplementation of essential amino acids (EAAs) (8 g/d over 1–3 months) significantly improves exercise intolerance of elderly patients with severe CHF/COPD, living at home or admitted to a Rehab setting.…”
Section: Introductionmentioning
confidence: 99%
“…This fact has been amply documented in animal [2427] and human studies, both in healthy subjects [28, 29] and in those suffering from chronic diseases associated with muscle depletion and different from stroke [3033]. …”
Section: Introductionmentioning
confidence: 99%